Tahfidz Quran Monitoring System in Islamic Boarding Schools - Syauqie Muhammad Marier; Pipit Febriana Dewi (Telematika, 2021)
Purpose: development a good tahfidz quran monitoring system, in presenting the data to quran teachers and parents. Presentation of data in the proposed monitoring system is in the form of tables, text, a graph of the Tahfidz progression and a dashboard for the achievement of the Tahfidz target.Design/methodology/approach: waterfallFindings/result: the tahfidz monitoring system that presents data in the form of graphs, charts, tables and text, thus providing monitoring functions that are easy to read and quickly understood.Originality/value/state of the art: dashboard display and chart on the tahfidz quran monitoring system